نموذج مقترح لمحاسبة الموارد البشرية في المؤسسة الاقتصادية - دراسة شركة سوف للدقيق- - معمري, اسلام; السخري, وسام; حمادي, وهيبة (University of eloued جامعة الوادي, 2018)
تتمحور موضوع دراستنا حول " نموذج مقترح لمحاسبة الموارد البشرية في المؤسسة الاقتصادية حيث هدفت هذه الدراسة إلى مدى أهمية العنصر البشري ومكانته في المؤسسة الاقتصادية، كيفية القياس والإفصاح عن محاسبة الموارد البشرية في المؤسسة، إظهار قيم الموارد البشرية بصورة تعكس كفايتها وتعطي مستخدمي الكشوفات المالية الصورة الواضحة التي يمكن من اتخاذ القرارات غير مضللة. ومن ابرز ما توصلنا إليه من نتائج : - الموارد البشرية استوفت شروط اعتبارها كأصل من أصول المنشاة وعلى هذا الأساس يمكن أن تظهر أرصدته في القوائم المالية دون الخروج عن مبادئ المحاسبية التقليدية. - يؤثر الإفصاح والقياس عن الموارد البشرية في اتخاذ القرارات المالية وذلك من خلال ظهوره في قائمة المركز المالي كأحد أصول المنشاة. - نظرا لوجود صعوبة في قياس الموارد البشرية وذلك لكثرة المتغيرات المتعلقة بالمورد البشري والتي تساهم في تحديده قيمته لم يتم الاتفاق على نموذج محدد لقياس هذه الموارد. - اعتبار الموارد البشرية أصلا يؤدي إلى زيادة ربح لشركة الدقيق سوف وكذا ارتفاع نسبة أرباح شركائها. - قد تؤثر الموارد البشرية سلبا على شركة سوف للدقيق من خلال ارتفاع الضريبة على أرباح الشركات IBS لها. The objective of this study is to examine the importance of the human factor and its place in the economic institution, how to measure and disclose the accounting of human resources in the institution, to show the values of human resources in a manner that reflects its adequacy and gives the users of the financial statements the clear picture Which can make decisions are not misleading. Among the most prominent findings we have reached: - Human resources have met the conditions of being considered as an asset of the entity and on this basis its assets can appear in the financial statements without departing from the traditional accounting principles . - Disclosure and measurement of human resources affect financial decision making by appearing in the statement of financial position as an asset of the entity . - Due to the difficulty in measuring human resources due to the many variables related to the human resource, which contributes to determining its value, no specific model has been agreed to measure these resources . - The consideration of human resources in the first place leads to an increase in profit for the flour company as well as the high profit rate of its partners. - Human resources may adversely affect the company's will through the high tax on the profits of its IBS companies
مذكرة ماستر محاسبة
Keywords: الموارد البشرية، محاسبة الموارد البشرية، القياس المحاسبي، الإفصاح المحاسبي; Human Resources, Human Resources Accounting, Accounting Measurement, Accounting Disclosure .